An Exploration of Factors that Discourage South African University Students’ Entrepreneurial Intention - (:unkn) unknown (My University, 2021)
Unemployment is a highly documented socio economic problem in South Africa. This problem is even worse amongst the youth of the country. As most young people go through tertiary institutions hoping to secure a source of income, they are met with the harsh realities of high youth unemployment upon the completion of their degrees. This leaves graduates with two choices: Create a business or stay unemployed and hope for an employment opportunity. This socio economic problem is not only present in South Africa as many developing countries are also experiencing it. This has led academics to inquire about what possible factors are discouraging the youth from starting their own business as a solution to the high unemployment rates. Even though entrepreneurship has been globally purported as the springboard in facilitating economic participation among youth, they face many stumbling blocks during their entrepreneurial journey.It was therefore the aim of the current study to uncover the factors that discourage youth entrepreneurial intentions at a university in South Africa. The study employed a quantitative research approach and data were collected using structured questionnaires from 247 participants and analysed using Factor analysis. After analysis, the results shows that, lack of business management skills, risk and economic difficulties, financial challenges, lack of a support system, uncertain future and difficulty in finding partners, bureaucracy and crime as well as lack of relevant information were the factors discouraging prospective young entrepreneurs in this university from engaging in entrepreneurial activities.
Keywords: African Research